Harnessing Artificial Intelligence and Its Impact on Pre-Service Teacher’s Technological, Pedagogical, and Content Knowledge Skills: A Meta-Analysis - Widowati, Asri; Zaida Ilma, Arina (Journal of Teaching and Learning, 2025)
As education shifts into the digital age, technology, especially artificial intelligence (AI), plays an increasingly vital role in improving teaching and learning. This meta-analysis investigates how AI impacts the development of Technological Pedagogical and Content Knowledge (TPACK) skills among pre-service teachers. By reviewing data from various studies published between 2010 and 2023, we explore how AI can help integrate technology into educational settings. Our findings reveal that AI interventions generally positively affect TPACK skills, although the extent of these effects varies significantly across studies. Factors such as sample size, duration of the intervention, and the quality of AI tools used all contribute to these differences. Importantly, larger sample sizes and well-designed AI applications lead to more significant improvements in TPACK skills. However, challenges still exist, particularly the need for adequate training and institutional support for pre-service teachers. This research highlights the necessity of establishing the best practices for incorporating AI into teacher training programs. By addressing the gaps in current literature, this study offers valuable insights into the effective use of AI in enhancing TPACK skills and advocates for further investigation in this critical area of educational technology.